Can We Measure the Transition to Reading? General Outcome Measures and Early Literacy Development From Preschool to Early Elementary Grades - Scott McConnell; Alisha Wackerle-Hollman (SAGE Publishing, 2015)
This study evaluated the extent to which existing measures met standards for a continuous suite of general outcome measures (GOMs) assessing children's early literacy from preschool through early elementary school. The study assessed 316 children from age 3 years (2 years prekindergarten) through Grade 2, with 8 to 10 measures of language, alphabetic principle, phonological awareness, and beginning reading. We evaluated measures at each grade group against six standards for GOMs extracted from earlier work. We found that one measure of oral language met five or six standards at all grade levels, and several measures of phonological awareness and alphabetic principle showed promise across all five grade levels. Results are discussed in relation to ongoing research and development of a flexible and seamless system to assess children's academic progress across time for effective prevention and remediation, as well as theoretical and empirical analyses in early literacy, early reading, and GOMs.